PERAMALAN PRODUKSI KELAPA SAWIT DENGAN METODE EXPONENTIAL SMOOTHING - Rahmadeni, Rahmadeni; Egianta, Anggun Nidia (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2024)
Oil palm is an important agricultural commodity that has a significant contribution to the global economy. One of the areas that produce oil palm plants in Indonesia is Riau province. Riau Province is the largest contributor to oil palm production on the island of Sumatra. Palm oil production always experiences changes in the increase and decrease in the amount of production. The purpose of this study is to determine the palm oil production data forecasting model. The method used in this research is the Exponential Smoothing method. Based on the research results obtained that with a MAPE of 7.63%, the Additive season Holt-Winter TES model shows a significant increase in forecasting accuracy compared to other models. So that the Holt-Winter TES model is the best model in forecasting palm oil production